The Diversity Of Waqf Implementations for Economic Development in Higher Education - Shaifull Anuar, Ahmad; Bahari, Zakaria; Doktoralina, Caturida Meiwanto; Indriawati, Fitri; Nugroho, Lucky (Universitas Islam Negeri Raden Intan Lampung, 2019)
ABSTRACTThe development of higher education in Malaysia is multiplying based on the increasing numbers of Public Higher Learning Institutions (IPTA) and Private Higher Learning Institutions (IPTS). This increase has encouraged various parties to collaborate to create a solid foundation and strategy to create IPT to become more competitive. However, the funding factor is still one restraint that IPTs must face. To overcome this problem, one example of IPT is taking the initiative by implementing waqf for higher education in limited institutions. Based on this scenario, the present paper was written to achieve two objectives:The first isto examine the precise development of higher education waqf that has been implemented in IPT in Malaysia. Thesecond isto precisely examine the variety of waqf that can be implemented for higher education. This study is an exploration in which the data used were derived from library research. The findings of this study will develop a theory on the diversification of waqf implementations for higher education in Malaysia. Keywords: Diversity, Economic, Instrument of Waqf, Waqf of Higher Education